Effect of wearing a swimsuit on hydrodynamic drag of swimmer - Marinho,Daniel Almeida (2012)
The purpose of this study was to analyse the effect of wearing a swimsuit on swimmer's passive drag. A computational fluid dynamics analysis was carried out to determine the hydrodynamic drag of a female swimmer's model (i) wearing a standard swimsuit; (ii) wearing a last generation swimsuit and; (iii) with no swimsuit, wearing light underwear. The three-dimensional surface geometry of a female swimmer's model with different swimsuit/underwear was acquired through standard commercial laser scanner. Passive drag force and drag coefficient were computed with the swimmer in a prone position. Higher hydrodynamic drag values were determined when the swimmer was with no swimsuit in comparison with the situation when the swimmer was wearing a swimsuit. The last generation swimsuit presented lower hydrodynamic drag values, although very similar to standard swimsuit. In conclusion, wearing a swimsuit could positively influence the swimmer's hydrodynamics, especially reducing the pressure drag component.